From Stimulus to Consolidation : Revenue and Expenditure Policies in Advanced and Emerging Economies - Clements, Benedict (Departmental Papers; Departmental Paper, 2010)
This paper identifies policy tools that could be used for fiscal consolidation in advanced and emerging economies in the years ahead. The consolidation strategy, particularly in advanced countries, should aim to stabilize age-related spending in relation to GDP, reduce non-age-related expenditure ratios, and increase revenues. Bold reforms are needed to offset projected increases in age-related spending, particularly health care. On the revenue side, measures could include improving tax compliance, for example through better international cooperation, as well as increasing the yield from VAT by eliminating exemptions and reduced rates, further developing property taxes, and increasing excise rates within the range of rates already applicable in comparable countries.